Why Do Planners Overlook Manufactured Housing and Resident-Owned Communities as Sources of Affordable Housing and Climate Transformation?. Issue 1 (2nd January 2023) - Lamb, Zachary; Shi, Linda; Spicer, Jason
Abstract: More Americans live in manufactured housing than in public and federally subsidized rental housing combined. Of the nearly 40, 000 U.S. manufactured housing communities (MHCs), more than 1, 000 are resident-owned communities (ROCs), a form of cooperative ownership. Yet planning research continues to neglect MHCs and ROCs, raising questions of classism and cultural bias. We address five common biases against MHCs and argue ROCs in particular deserve greater attention because they enable low-income people to improve their housing security in the face of financial and environmental vulnerabilities. Lessons from these efforts can help other alternative and collective housing providers do the same.